Game over or play again? Deploying games for promoting water recycling and hygienic practices at schools in Ethiopia. Issue 111 (September 2020) - Kragić Kok, Darja; Bisschops, Iemke; Knoop, Lenneke; Tulu, Lemma; Kujawa-Roeleveld, Katarzyna; Masresha, Nardos; Houtkamp, Joske
Highlights: Drawing on theories used in gamification of learning, four educational games for improvement of school WaSH in Ethiopia were developed and tested. The games promote hygienic practices and water conservation in schools by introducing low-cost treatment and reuse of handwashing wastewater. There is a large potential for development, use, and upscaling of educational games for more sustainable WaSH interventions. Abstract: Worldwide, every year 525 000 children under the age of five die from diarrhoea. The simple act of washing hands with soap and water can prevent more than one-third of diarrhoeal disease cases. In the densely populated urban areas of the developing world, handwashing wastewater is commonly discharged to the environment without any treatment, creating unhygienic situations and breeding places for different vectors and wasting a valuable resource. However, this relatively clean wastewater can be treated and reused using simple technological solutions. The objective of our water innovation is, therefore, twofold: improving children's health through stimulating handwashing at schools while at the same time demonstrating the feasibility of water conservation through low-tech, nature-based treatment and safe reuse of handwashing wastewater for irrigation and toilet flushing. To enhance the intrinsic motivation of children and school staff to adopt this innovation, four educational games were developed drawing on theories used in gamification of learning, such as social learning theory and engagement theories. This paper provides an overview of the games and the main results of the game testing. For promoting hygiene among school children, a board and a card game were developed based on the F-diagram – commonly used by water and sanitation practitioners to illustrate the main routes for pathogen transmissions from faeces. In addition, the system linking handwashing wastewater collection, treatment and reuse for irrigation and toilet flushing was simulated by the development of two board games which targeted school children, school staff and the operators of the treatment system. The prototypes and final versions were tested in two schools in the Oromia region in Ethiopia – while the treatment system (constructed wetland) for handwashing wastewater is located in one school. Children that play-tested the games were generally enthusiastic and eager to play repeatedly, which demonstrated that board and card games are appropriate tools to engage with this young target group. We conclude that there is a large potential for development, use, and upscaling of educational games for more sustainable WaSH interventions.